2017
DOI: 10.1021/acs.analchem.7b04014
|View full text |Cite
|
Sign up to set email alerts
|

A Pumpless Acoustofluidic Platform for Size-Selective Concentration and Separation of Microparticles

Abstract: We have designed a pumpless acoustofluidic device for the concentration and separation of different sized particles inside a single-layered straight polydimethylsiloxane (PDMS) microfluidic channel. The proposed device comprises two parallel interdigitated transducers (IDTs) positioned underneath the PDMS microchannel. The IDTs produce high-frequency surface acoustic waves that generate semipermeable virtual acoustic radiation force field walls that selectively trap and concentrate larger particles at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…[1][2][3][4][5][6] Acoustofluidic technologies, which combine acoustics and microfluidics, have demonstrated promising potential for the design and integration of POC technologies. [7][8][9][10][11][12] Acoustofluidic technologies have the capability of interacting with fluidic environments in a contact-free and precise manner; 13,14 this capability has been leveraged to achieve many useful applications in biology and medicine including sample concentration, 15,16 sample mixing, [17][18][19] sample delivery, 20 and cell/particle separation. 7,21,22 While all of these factors make acoustofluidic devices excellent candidates for use at the POC, one of the major draw-backs associated with acoustofluidic devices is the additional equipment needed to operate effectively; commonly, acoustofluidic devices rely on bulky and expensive function generators for signal generation, amplifiers for increasing the signal power, syringe pumps for precise fluid manipulation, and microscopes for microscale imaging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] Acoustofluidic technologies, which combine acoustics and microfluidics, have demonstrated promising potential for the design and integration of POC technologies. [7][8][9][10][11][12] Acoustofluidic technologies have the capability of interacting with fluidic environments in a contact-free and precise manner; 13,14 this capability has been leveraged to achieve many useful applications in biology and medicine including sample concentration, 15,16 sample mixing, [17][18][19] sample delivery, 20 and cell/particle separation. 7,21,22 While all of these factors make acoustofluidic devices excellent candidates for use at the POC, one of the major draw-backs associated with acoustofluidic devices is the additional equipment needed to operate effectively; commonly, acoustofluidic devices rely on bulky and expensive function generators for signal generation, amplifiers for increasing the signal power, syringe pumps for precise fluid manipulation, and microscopes for microscale imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Acoustofluidic technologies have the capability of interacting with fluidic environments in a contact-free and precise manner; 13,14 this capability has been leveraged to achieve many useful applications in biology and medicine including sample concentration, 15,16 sample mixing, [17][18][19] sample delivery, 20 and cell/particle separation. 7,21,22 While all of these factors make acoustofluidic devices excellent candidates for use at the POC, one of the major draw-backs associated with acoustofluidic devices is the additional equipment needed to operate effectively; commonly, acoustofluidic devices rely on bulky and expensive function generators for signal generation, amplifiers for increasing the signal power, syringe pumps for precise fluid manipulation, and microscopes for microscale imaging. 13,14,17,23,24 Although acoustofluidic devices are presented as simple solutions to complex problems, each of these external systems introduce operational constraints that hinder the use of acoustofluidic technology at the POC, making the technology less approachable to researchers and clinicians who could benefit from it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, these methods can be divided into two main categories: active and passive. Using active methods, an external force field in electrical, magnetic, and acoustic forms is applied for separation. With passive methods, there is no external factor involved in the separation process .…”
Section: Introductionmentioning
confidence: 99%
“…Cole et al [ 12 ] demonstrated a kind of DEP microfluidics that combined the flexibility and programmability of microliter dispensing with the scalability and single-cell sensitivity of flowing droplet microfluidics. Acoustic and optical forces have also been utilized for particle [ 13 , 14 ] and droplet [ 15 , 16 , 17 ] manipulation. Optical tweezers [ 18 ] are a typical tool for single cell manipulation, which use a highly focused laser beam to provide an attractive or repulsive force.…”
Section: Introductionmentioning
confidence: 99%